Brain morphometric changes in children born as small for gestational age without catch up growth - Takatani, Tomozumi; Shiohama, Tadashi; Takatani, Rieko; Hattori, Shinya; Yokota, Hajime; Hamada, Hiromichi (Frontiers in Neuroscience, 2024)
Introduction Most infants born as small for gestational age (SGA) demonstrate catch up growth by 2–4 years, but some fail to do so. This failure is associated with several health risks, including neuropsychological development issues. However, data on the morphological characteristics of the brains of infants born as SGA without achieving catch up growth are lacking. This study aims to determine the structural aspects of the brains of children born as SGA without catch up growth. Methods We conducted voxel- and surface-based morphometric analyses of 1.5-T T1-weighted brain images scanned from eight infants born as SGA who could not achieve catch up growth by 3 years and sixteen individuals with idiopathic short stature (ISS) to exclude body size effects. Growth hormone (GH) secretion stimulation tests were used to rule out GH deficiency in all SGA and ISS cases. The magnetic resonance imaging data were assessed using Levene’s test for equality of variances and a two-tailed unpaired t-test for equality of means. The Benjamini–Hochberg procedure was used to apply discovery rate correction for multiple comparisons. Results Morphometric analyses of both t-statical map and surface-based analyses using general linear multiple analysis determined decreased left insula thickness and volume in SGA without catch up growth compared with ISS. Conclusion The brain scans of patients with SGA who lack catch up growth indicated distinct morphological disparities when compared to those with ISS. The discernible features of brain morphology observed in patients born as SGA without catch up growth may improve understanding of the association of SGA without catch up growth with both intellectual and psychological outcomes.